OVERVIEW OF ATTITUDES REGARDING DAILY SKILLS POWERED BY GENDER IN GEN Z - Meinarisa, Meinarisa; Nasution, Riska Amalya; Martawinarti, RTS Netisa; Mawarti, Indah; Kamariyah, Kamariyah; Sari, Putri Irwanti (Jurnal Keperawatan Universitas Jambi, 2026)
Background : This study focuses on attitudes regarding daily skills mastered by each gender in Gen Z. The Methods : research method in this study is a quantitative descriptive research method. Data collection using a digital questionnaire (google form). The population in this study amounted to 325 respondents using a simple random sampling technique. Results : The characteristics of the respondents above present the largest gender data is male, which is 179 (55%). The age of the largest respondents is 20 years old as many as 114 (35%). Most respondents 227 (70%) have never received gender education and most respondents' education is bachelor 247 (76%). Attitudes towards Daily Skills that must be mastered by each gender according to Gen Z on the statement of being able to prepare daily food to eat, most respondents agree 306 (94%). The ability to clean the house, most respondents agree to be mastered 318 (97%). The ability to wash dirty clothes, most respondents agree to be mastered 300 (92%). The ability to clean the toilet, most respondents agree to be mastered 290 (89%). The ability to take care of family/siblings/younger siblings, most respondents stated that they agreed to be mastered 264 (81%). Conclusion : The results of the study showed that Gen Z has an attitude that agrees that every gender must be able to master daily skills. For further research, research can be conducted by looking at the implementation of these abilities or Gen Z's behavior towards the ability to master daily skills. Keywords : Skills, Attitudes, Gen Z, Gender